Establishment of plasmid vector and allelic exchange mutagenesis systems in a mycobacterial strain that is able to degrade polycyclic aromatic hydrocarbon. Issue 7 (3rd July 2018) - Kishida, Kouhei; Ogawa, Natsumi; Ichihashi, Eikichi; Kato, Hiromi; Nagata, Yuji; Ohtsubo, Yoshiyuki; Tsuda, Masataka
Abstract: Plasmid vector and allelic exchange mutagenesis systems were established for the genetic analysis of a phenanthrene-degrading mycobacterial strain, Mycobacterium sp. EPa45. Successful application of these systems revealed the necessity of the EPa45 phdI gene for the degradation of 1-hydroxy-2-naphthoate, which has been proposed to be an intermediate product in the degradation pathway of phenanthrene.